Review of the Trifolium amabile Complex in Peru, with the Description of a New Species - Eduardo Antonio Molinari-Novoa (Scientifica)
Here, we describe Trifolium absconditum sp. nov., a new species of the T. amabile complex from South America. It differs from other Peruvian Trifolia of the complex by having smaller stipules, leaves, inflorescences, and floral pieces. A key for Peruvian species of the complex is presented, and typifications for them are made when necessary and material is available in Peruvian herbaria. Thus, the number of Peruvian species in the complex is elevated to three: T. amabile, T. absconditum, and a resurrected T. peruvianum. Finally, it is suggested that Chile must be excluded from the distribution of this complex.